Causal associations between liver function biomarkers and prostate cancer risk in European and East Asian populations: a univariate, multivariable, and bidirectional Mendelian Randomization study - Xinyu Xu; Wenjing Zhu; Yu Peng (Discover Oncology)
Abstract Background Previous observational studies have indicated a potential association between liver function markers and prostate cancer (PCa), but the causal relationship of this association remains unclear. Additionally, genetic variations across populations may influence the direction and strength of this association. This study employed Mendelian Randomization (MR) to investigate the genetic causal relationship between liver function markers and PCa in European and East Asian populations. The aim was to uncover potential gene-disease associations across ancestries and provide novel insights for the prevention and treatment of PCa. Methods Single nucleotide polymorphisms (SNPs) significantly associated with liver function markers and PCa were selected from large-scale genome-wide association studies (GWAS) as instrumental variables (IVs). Univariate, multivariable, and bidirectional MR analyses were conducted to evaluate the causal relationships between liver function markers and PCa. The inverse variance weighting (IVW) method was used as the primary MR approach, complemented by sensitivity analyses to ensure the robustness and reliability of the findings. Results In European populations, univariate MR analysis suggested that ALT (OR 0.85, 95% CI 0.75–0.95, P = 0.005) and AST (OR 0.90, 95% CI 0.81–1.00, P = 0.045) were associated with a reduced risk of PCa. However, multivariable MR analysis, after adjusting for confounders, showed that these associations were no longer statistically significant. Reverse MR analysis provided no evidence supporting a causal effect of PCa on liver function markers in European populations. Sensitivity analyses revealed heterogeneity in the IVs but did not detect evidence of horizontal pleiotropy. In East Asian populations, total bilirubin (OR 0.94, 95% CI 0.88–1.00, P = 0.049) and direct bilirubin (OR 0.91, 95% CI 0.84–0.99, P = 0.022) were causally associated with a reduced risk of PCa. After adjusting for confounders in multivariable MR, the association between total bilirubin and PCa remained significant (OR 0.74, 95% CI 0.55–0.99, P = 0.044). Reverse MR analysis suggested a causal effect of PCa on reduced ALT levels (OR 0.93, 95% CI 0.88–0.98, P = 0.007). Sensitivity analyses did not reveal heterogeneity or horizontal pleiotropy. Conclusion The relationship between liver function markers and PCa seems to be influenced by genetic background. In East Asian populations, total bilirubin was identified as an independent protective factor against PCa, while reverse MR suggested a causal effect of PCa on reduced ALT levels. In European populations, there was insufficient evidence for a causal relationship between liver function markers and the risk of PCa. These findings may inform strategies for the clinical prevention, monitoring, and treatment of PCa, and further research is warranted to elucidate the underlying mechanisms driving these associations.